Case Report: Peritoneal and small bowel metastasis from lung adenocarcinoma with EGFR L858R mutation - Tan, Tian; Huang, Yuerong; Yan, Rongxin; Liu, Ying (Frontiers in Oncology, 2025)
Recently, cases of lung cancer metastasizing to atypical sites, such as the small intestine and colon, have been reported; however, peritoneal metastasis remains uncommon. Herein, we present the case of a patient with stage IV lung adenocarcinoma with an EGFR L858R mutation, who developed peritoneal metastasis involving the small intestine, leading to intestinal obstruction and death following osimertinib resistance.